2018
DOI: 10.1007/s12034-018-1624-0
|View full text |Cite
|
Sign up to set email alerts
|

On the structural and electrical properties of metal–ferroelectric–high k dielectric–silicon structure for non-volatile memory applications

Abstract: In this article, we report the structural and electrical properties of metal-ferroelectric-high k dielectric-silicon (MFeIS) gate stack for non-volatile memory applications. Thin film of sputtered SrBi 2 Nb 2 O 9 (SBN) was used as ferroelectric material on 5-15 nm thick high-k dielectric (Al 2 O 3 ) buffer layer deposited using plasma-enhanced atomic layer deposition (PEALD). The effect of annealing on structural and electrical properties of SBN and Al 2 O 3 films was investigated in the temperature range of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…From the graph, it has been observed that the minimum leakage current density is order of 10 −5 -10 −6 A cm −2 at − 7 V in the annealing temperature ranging from 400 to 600 °C. A minimum leakage current density has been observed at the annealing temperature of 500 °C which signifies that there is low trap density, improvement in interface at BFO/Si and deposited film properties [45]. At 500 °C, the minimum current density is observed at gate voltage of − 1 V due to direct tunnelling of charge carriers through defects present in the annealed film.…”
Section: Metal/ferroelectric/siliconmentioning
confidence: 88%
“…From the graph, it has been observed that the minimum leakage current density is order of 10 −5 -10 −6 A cm −2 at − 7 V in the annealing temperature ranging from 400 to 600 °C. A minimum leakage current density has been observed at the annealing temperature of 500 °C which signifies that there is low trap density, improvement in interface at BFO/Si and deposited film properties [45]. At 500 °C, the minimum current density is observed at gate voltage of − 1 V due to direct tunnelling of charge carriers through defects present in the annealed film.…”
Section: Metal/ferroelectric/siliconmentioning
confidence: 88%
“…Actually, reduced leakage current is obtained because of low trap density and better electron mobility for 600 • C device compared to 800 • C annealed device. As-formed device found increment in the trap density which results in trap assisted tunneling that increases the leakage current and decreases the non-volatile performance of the device [33]. Figure 4 (b) shows the interface level traps (Dit) with respect to E-Ev curvature of as-formed and annealed devices.…”
Section: ) Analysis Based On Non-volatile Characteristics Of Devicesmentioning
confidence: 99%